Process Optimization and Properties of Crude Gelatin Extracted from Tannery Bovine Hide - Talapphet, Natchanok; Prommajak, Trakul; Raviyan, Patcharin (Food and Applied Bioscience Journal, 2017)
Underutilized bovine hide from the tannery industry was investigated for the optimum conditions for extraction and the properties of gelatin. Central composite design and response surface methodology were employed to determine the effect of temperature of extraction (60°C to 80°C) and time of extraction (6 h to 48 h) on the yield and the gel strength of crude gelatin. The optimum condition was found to be extraction from delimed skin with 0.15 M acetic acid at 70°C for 6 h, which resulted in a gelatin yield of 4.78% and gel strength of 265.45 g. The crude gelatin consisted of low molecular weight components with protein bands between 6 kDa and 38 kDa. The overall properties were found to fall within the product standard, though the values of gel strength, viscosity, and foaming properties were lower than the values for commercial halal bovine gelatin. It can be concluded that tannery bovine hide could be a potential raw material for production of low bloom gelatin.